(untitled) (Research, Society and Development, 2021)
The objective was to verify the impact of the equine therapy sports program on the flexibility, strength and balance of people with intellectual disabilities. Six individuals participated in the study with a mean age of 17.5 ± 2.07 years. The attendance were made once a week, for 30 minutes, the english saddle was used with the horse at a trot. Wells’ block was used to assess flexibility, the Sit and Stand test and the lumbar dynamometer to assess muscle strength, and the Clinical Balance Sensory Integration test. Differences with a p-value equal to or less than 5% were considered statistically significant. The results showed significance in muscle flexibility (p = 0.026), muscle strength through the Sit and Stand test (p = 0.004), lumbar dynamometer (p = 0.014) and balance (p = 0.045), after ten attendance. We conclude the hippotherapy program for sports contributed to the development and physical performance of these subjects.